A closer look at the bread making process and the quality of bread as a function of the degree of preharvest sprouting of wheat (Triticum aestivum). (March 2018) - Olaerts, Heleen; Vandekerckhove, Laurence; Courtin, Christophe M.
Abstract: In this study, the impact of the extent of field sprouting of wheat on bread making and bread quality was investigated. Wheat with a flour Falling number (FNflour ) down to 200 s was still manageable during bread making on laboratory scale. In contrast, the use of severely sprouted wheat (FNflour below 200 s) resulted in sticky dough and bread with impaired crumb texture, high crumb stickiness, and darker crust color. Loaf volume was positively affected by increased α-amylase activity leading to a prolonged dough rise during the baking phase, but excess α-amylase activity resulted in collapse of the bread structure. The increased α-amylase activity largely hydrolyzes starch during baking resulting in a decreased gel forming capacity of starch during cooling, leading to high crumb stickiness and poor crumb texture. Excessive darkening of the bread crust and dough stickiness was associated with an increase in activity of α-amylases and endoxylanases. Peptidases presumably only played a role during dough mixing of sprouted wheat flour. Baking of high enzyme flours due to preharvest sprouting poses a serious challenge to the industry. Highlights: The extent of preharvest sprouting is determinative for bread loaf volume. High α-amylase activity leads to sticky doughs, poor bread crumb texture, and dark crust. Excessive crust color formation is associated with elevated α-amylase and endoxylanase activities. Peptidases presumably only played a role during dough mixing of sprouted wheat flour. Baking of high enzyme flours poses a serious challenge to the industry.